DAMPAK KEBIJAKAN PEMBATASAN SOSIAL TERHADAP KINERJA PENDAPATAN RESTORAN DI PROVINSI BALI - Cahyadi, Ni Made Ayu Krisna; Prima, Suci Rahmawati (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.04.TAHUN.2022DO - 10.24843/EEB.2022.v11.i04.p08, 2022)
The Covid-19 pandemic has a major impact on the development of the Indonesian economic. Several business sectors, particularly in the industrial and service sectors, experienced a drastic decline in their performance due to the policy of restricting the mobility of goods and services. This policy was adopted by the government as a step to prevent and reduce the spread and number of Covid-19 cases. The province of Bali, which is synonymous with tourism industry and services is the area with the deepest impact in Indonesia. The Accommodation and Food and Drink Provision Sector, which has been the main contributor in terms of the business sector, experienced a contraction of -27.52%. The purpose of this study is to observe the extent of the impact of these restrictive policies on the performance of restaurant income as one of the main sub-sectors in Bali Province. The data analysis technique used is panel data regression using primary data and also data processing result using Google Mobility Index. The research sample was 97 restaurants spread across 9 regencies/cities in Bali Province. Meanwhile, for the social restriction policy variable, a dummy variable is used. The results showed that there were differences in restaurant performance when there was no restriction policy and when there was a restriction policy.